BUILDING A CUSTOMER BENEFIT MODEL DRIVEN BY CUSTOMER SATISFACTION AND CUSTOMER LOYALTY BASED ON DIGITAL EXPERIENCE - Abdillah, Luthfi; Asnawi, Nur; Yuliana, Indah (EL DINAR: Jurnal Keuangan dan Perbankan Syariah, 2024)
Intense competition in the banking industry drives Islamic banks to offer digital services, boosting their performance and competitiveness. Digitization requires evaluation to measure the expected level of success. This study aims to assess the success of digital banking services in Islamic banks, considering not only financial gains, but also Maqashid Shariah-based indicators. Using the information system success model theory approach, the research began with an evaluation of the dimensions of the digital Shariah bank experience. Subsequently, we examined their influence on customer loyalty and customer satisfaction, as well as the impact of customer loyalty and customer satisfaction on customer benefit, based on Maqashid Shariah. Using a quantitative approach with purposive sampling techniques, data were collected using a questionnaire. Responses from 443 respondents were analyzed using PLS-SEM. The study indicates that the success of digitization can be measured by customer satisfaction and loyalty, based on factors such as service quality, convenience, security, trust, innovation, value, and Sharia compliance, all aligned with Maqashid Shariah principles. Customer loyalty outweighs satisfaction with driving benefits. Hence, enhancing the digital Shariah bank experience is prioritized for successful Sharia digital banking, aiming at sustainable benefits.